Lexical Metaphors and Cultural Defense: How Karo Youths Preserve Tradition through 'Minyak Pengalun' - Tarigan, Karisma Erikson (LingPoet: Journal of Linguistics and Literary Research, 2025)
The aim of this study is to explore the role of lexical metaphors in the preservation of cultural heritage among Karo youths, focusing on the traditional practice of using "Minyak Pengalun," a medicinal oil deeply embedded in the Karo people's ecological and cultural identity. A qualitative research design was employed, utilizing semi-structured interviews and document analysis as the primary methods of data collection. Interviews were conducted with Karo adolescents, cultural experts, and traditional healers, while traditional Karo texts were analyzed to identify metaphors associated with "Minyak Pengalun." The results indicate that Karo youths have a deep understanding of the metaphors associated with "Minyak Pengalun," using them actively in cultural practices as a form of cultural resistance. The study also highlights the importance of these metaphors in maintaining Karo cultural identity and ecological knowledge. In conclusion, Karo youths play a critical role in the defense and preservation of their cultural heritage through the active use of lexical metaphors. However, challenges such as the influence of modernity require strategies like cultural education programs to strengthen the connection between Karo youths and their traditions.